1987
DOI: 10.1007/bf00275746
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of the effects of insulin and insulin-like growth factors I and II on glucose uptake in cultured rat skeletal muscle cells by sulfonylureas

Abstract: Summary. The effect of sulfonylureas on long-term regulation of glucose uptake by insulin and insulin-like growth factors has been studied in the L6 line of cultured skeletal muscle cells. These cells have previously been shown to possess many characteristics of differentiated skeletal muscle and to bind and respond to physiological concentrations of insulin and insulin-like growth factors I and II. Tolazamide (halfmaximal at 0.2 mg/ml) augments the effects of insulin, insulin-like growth factor I, and insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…The previously published observation that tolazamide increases the maximal efficacy of insulin rather than increasing insulin sensitivity also is consistent with a postbinding mechanism of action (14).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The previously published observation that tolazamide increases the maximal efficacy of insulin rather than increasing insulin sensitivity also is consistent with a postbinding mechanism of action (14).…”
Section: Resultssupporting
confidence: 85%
“…Actions of sulfonylureas on glucose utilization by peripheral tissues have been demonstrated by in vivo clamp studies in type II diabetes (12) and are further evidenced by the decreased insulin requirements of type I diabetics treated with both sulfonylureas and insulin (13). We have recently observed that sulfonylureas augment insulin-stimulated glucose uptake in cultured L6 skeletal muscle cells (14). Consistent with in vivo findings (15), sulfonylureas had no effect on the rate ofglucose transport in L6 cells in the absence ofinsulin.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations